Misi Oikumenis: Mendialogkan Kearifan Lokal Ma’bua Kalebu dengan Yohanes 17: 21 dalam Relasi antar Denominasi Gereja di Seko Lemo - Ferialdi Agasta; Ardano, Lucky; Wingki, Wingki; Panandu, Filadelvia (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
This paper aims to find aspects of ecumenical mission in the local wisdom of ma'bua kalebu in Seko Lemo. The diverse teachings of church dogmatics today often trigger disharmonious relations between churches and tend to criticize each other's church members. By looking at this situation, the problem no longer shows Jesus' hope in John 17: 20-23 that all his disciples would be one just as he and the Father are one. In contrast to this situation, it seems that the relationship between the churches in Seko Lemo is very harmonious. This article uses qualitative research through a descriptive approach with observation and interviews and literature study. The study found that the local wisdom of ma'bua kalebu shows parallels with the concept of ecumenical mission according to John 17:20-23. This is because the basic essence of ma'bua kalebu in the Seko Lemo community is to support the harmony and unity of the community, to keep the community abiding by the prevailing norms, and as a medium of resolution when problems occur in the community. This local wisdom has a strong influence in uniting communities, families, and religious life in Seko Lemo.